Current concepts of diagnosis and management of ACL injuries in skeletally immature athletes - Finlayson, C. J.; Nasreddine, A.; Kocher, M. S. (The Physician and Sportsmedicine, 2010)
Abstract: Anterior cruciate ligament (ACL) injuries in skeletally immature athletes are encountered with increasing frequency. The management of such injuries is controversial. Nonsurgical management often results in functional instability and a higher risk of meniscal and chondral injury to the knee. Conventional methods of ACL reconstruction carry the risk of growth disturbance because of iatrogenic damage to the physes around the knee. Multiple cases of growth disturbance have been reported. This article discusses the relevant anatomy, natural history, risk factors, treatment, and prevention of ACL injuries in skeletally immature patients. Surgical treatment is based on physiologic age. For prepubescent patients, we recommend physeal-sparing combined intra-articular/extra-articular reconstruction with autogenous iliotibial band. In adolescent patients with significant growth remaining, we recommend transphyseal ACL reconstruction with hamstrings autograft and fixation away from the physes. In older adolescent patients, we recommend conventional adult ACL reconstruction with autogenous hamstrings or patellar tendon.